2021
DOI: 10.1016/j.jns.2021.117517
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid in COVID-19 neurological complications: Neuroaxonal damage, anti-SARS-Cov2 antibodies but no evidence of cytokine storm

Abstract: Objective To study in cerebrospinal fluid (CSF) of COVID-19 subjects if a “cytokine storm” or neuroinflammation are implicated in pathogenesis of neurological complications. Methods Cross-sectional study of CSF neuroinflammatory profiles from 18 COVID-19 subjects with neurological complications categorized by diagnosis (stroke, encephalopathy, headache) and illness severity. COVID-19 CSF was compared with CSF from healthy, infectious and neuroinflammatory disorders and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 69 publications
5
54
1
Order By: Relevance
“…Using cerebrospinal fluid may have had a higher predictive value [ 57 , 116 , 117 , 118 ]. Elevations in serum NF-L levels were reported inconsistently in studies plagued with small fibers, unadjusted for comorbidities, or limited to the most sick patients [ 12 , 32 , 35 , 94 , 119 , 120 , 121 ]. Gisslen et al reported the normalization of GFAP and NF-L six months after the resolution of COVID-19, but their patients continued to exhibit neurological symptoms and their study was limited to these markers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using cerebrospinal fluid may have had a higher predictive value [ 57 , 116 , 117 , 118 ]. Elevations in serum NF-L levels were reported inconsistently in studies plagued with small fibers, unadjusted for comorbidities, or limited to the most sick patients [ 12 , 32 , 35 , 94 , 119 , 120 , 121 ]. Gisslen et al reported the normalization of GFAP and NF-L six months after the resolution of COVID-19, but their patients continued to exhibit neurological symptoms and their study was limited to these markers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple cytokines were found to be elevated in the blood during acute COVID-19, while increased levels of proinflammatory markers were not detected in the cerebrospinal fluid (CSF) [ 41 ]. Serum levels of IL-4, IL-10, IL-6 and IL1β were elevated in COVID-19 patients [ 33 , 42 , 43 ].…”
Section: Chaptermentioning
confidence: 99%
“…SARS-CoV-2 antibodies were frequently detected in the CSF of COVID-19 patients, although this does not prove intrathecal antibody production [ 41 , 44 , 45 ]. The detection of the virus via PCR from CSF was impossible in most cases [ 41 , 44 , 45 ].…”
Section: Chaptermentioning
confidence: 99%
See 1 more Smart Citation
“…Biomarker analyses of cerebrospinal fluid consistently demonstrates abnormal CSF to plasma albumin ratio in a portion of patients with acute SARS-CoV2 infection suggesting breakdown of the BBB during acute infection, particularly in patients experiencing severe SARS-CoV2 infection. Additionally, neurofilament light chain, a marker of neuronal injury, is found to be elevated in the CSF of patients with acute SARS-CoV2 infection and is higher in individuals with severe SARS-CoV2 infection [ 38 ]. These data suggest that severe, acute SARS-CoV2 infection may result in BBB breakdown and that this process may allow for the extravasation of immune cells or inflammatory cytokines into the CNS space with the potential to cause neuronal injury.…”
Section: Cerebrospinal Fluid Abnormalities In Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%